2021
DOI: 10.3390/ani11030819
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ambient Temperature Sample Storage on the Equine Fecal Microbiota

Abstract: Sample storage conditions are an important factor in fecal microbiota analyses in general. The objective of this study was to investigate the effect of sample storage at room temperature on the equine fecal microbiota composition. Fecal samples were collected from 11 healthy horses. Each sample was divided into 7 sealed aliquots. One aliquot was immediately frozen at −80 °C; the remaining aliquots were stored at room temperature (21 to 22 °C) with one transferred to the freezer at each of the following time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In contrast, a recent publication by de Bustamante et al found that aliquots of 2–3 g of feces stored in closed 118 mL containers for up to 6 h at room temperature prior to freezing did not affect the composition of the microbial population in equine feces, as compared to samples frozen immediately after collection. The same study also found that microbial populations were significantly changed by storage at ambient temperatures for periods longer than 6 h prior to freezing [ 12 ]. Samples from this de Bustamante et al study were not used to form inoculum to digest forages.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent publication by de Bustamante et al found that aliquots of 2–3 g of feces stored in closed 118 mL containers for up to 6 h at room temperature prior to freezing did not affect the composition of the microbial population in equine feces, as compared to samples frozen immediately after collection. The same study also found that microbial populations were significantly changed by storage at ambient temperatures for periods longer than 6 h prior to freezing [ 12 ]. Samples from this de Bustamante et al study were not used to form inoculum to digest forages.…”
Section: Discussionmentioning
confidence: 99%
“…However, this means that the T 0 samples were kept for a longer period (45–60 min), refrigerated at 4 °C, in regard to the T 3 samples, which could have altered the bacterial viability. Bustamante et al, 2021 revealed that storage of equine fecal samples at room temperature for up to 6 h before freezing had a minimal effect on the fecal microbiota [ 41 ]. Furthermore, Burz et al, 2019 showed that refrigeration at 4 °C can be a safe solution to avoid changes in bacterial populations during fecal sample storage for 24 h, which supports the result that the differences in the storage times in our study seem negligible [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this study, samples were transported back to the laboratory where the stool could be weighed and aliquoted inside a Class II biological cabinet. As the total processing time was under 6 h, it was assumed that any changes to the microbiota would have been insignificant [10,11]. However, future studies where samples are placed directly into commercial stool storage kits on the farm would be useful for replicating what would be done in a clinical setting.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, it must be considered that, in a farm setting, there may be limited access to cold storage. Therefore, it is not unusual for samples to remain at ambient temperature for prolonged periods before they reach the laboratory for analysis, resulting in the growth of minor species in the samples and a distortion of the true composition of the microbiota [7,[10][11][12][13][14]. Better methods of preserving bovine faecal microbiota are, therefore, required, particularly one that does not involve freezing the sample and is not reliant on immediate refrigeration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation